2013
DOI: 10.1593/tlo.13346
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ACEI/ARB and β-Blockers Is Associated with Improved Survival and Decreased Tumor Progression and Hospitalizations in Patients with Advanced Colon Cancer

Abstract: We have observed an association between exposure to a combination of ACEI/ARB + BB and increased survival, decreased hospitalizations, and decreased tumor progression in advanced colorectal cancer. Future studies will be needed to replicate these results and generalize them to broader populations. Determination of causality will require a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 31 publications
2
38
1
1
Order By: Relevance
“…Antihypertensive agents include angiotensin‐converting enzyme inhibitors (ACEIs), angiotensin receptor antagonists/blockers (ARBs) and beta‐blockers (these will be reviewed later) and are typically prescribed to treat hypertension, congestive heart failure and diabetic nephropathy. ACEIs reduce the production of angiotensin II, whereas ARBs selectively inhibit the activation of the angiotensin II type 1 receptor . Angiotensin II plays an important role in the regulation of fluid and electrolyte balance and is also involved in cell growth, differentiation, apoptosis and angiogenesis .…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antihypertensive agents include angiotensin‐converting enzyme inhibitors (ACEIs), angiotensin receptor antagonists/blockers (ARBs) and beta‐blockers (these will be reviewed later) and are typically prescribed to treat hypertension, congestive heart failure and diabetic nephropathy. ACEIs reduce the production of angiotensin II, whereas ARBs selectively inhibit the activation of the angiotensin II type 1 receptor . Angiotensin II plays an important role in the regulation of fluid and electrolyte balance and is also involved in cell growth, differentiation, apoptosis and angiogenesis .…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…A number of retrospective analyses have investigated the impact of antihypertensive treatment on patient outcome in several cancers . Cardwell et al reported on the use of ACEIs and/or ARBs after diagnosis with either breast, colorectal or prostate cancer in over 20 000 patients in the UK .…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Three articles were excluded as no usable data were reported (Wilop et al, 2009;Sendur et al, 2012;Moser et al, 2014). Three studies were also excluded as their reported data were not restricted to prediagnosis or postdiagnosis (Ganz et al, 2011;Engineer et al, 2013;Grytli et al, 2013). We further excluded four studies (Fletcher et al, 1993;Shah et al, 2011;Springate et al, 2015;Wong et al, 2015) that compared the effect of β blockers with that of other antihypertensive medications.…”
Section: Resultsmentioning
confidence: 99%
“…A number of epidemiologic studies have attempted to link the use of β blockers to mortality in patients with several cancer types including melanoma (Lemeshow et al, 2011;Livingstone et al, 2013;De Giorgi et al, 2014;McCourt et al, 2014;Moser et al, 2014), breast (Powe et al, 2010;Barron et al, 2011;Ganz et al, 2011;Melhem-Bertrandt et al, 2011;Sendur et al, 2012;Botteri et al, 2013;Cardwell et al, 2013;Holmes et al, 2013aHolmes et al, , 2013bSakellakis et al, 2015), colorectal (Engineer et al, 2013;Hicks et al, 2013;Holmes et al, 2013b;Jansen et al, 2014), prostate (Grytli et al, 2013(Grytli et al, , 2014Holmes et al, 2013b;Assayag et al, 2014;Cardwell et al, 2014), ovarian (Diaz et al, 2012;Johannesdottir et al, 2013), and lung cancer (Wilop et al, 2009;Aydiner et al, 2013;Wang et al, 2013;Holmes et al, 2013b;Cata et al, 2014); some have indicated that β-blocker use was associated with longer survival, whereas others showed no effect or a harmful effect. To date, no meta-analysis has investigated the impact of β-blocker use on the survival of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Az ACE-gátló/ARB kezelés hatását vizsgál-va a colorectalis daganatok kockázata szempontjából [52] kiderült, hogy a tartós, nagy dózisú kezelések a colorectalis daganatok incidenciájának csökkenését eredményezhetik. A két RAS-gátló kombinált alkalmazásának kedvező hatása kimutatható volt mind a mortalitásra, mind pedig a túlélésre [53]. Más vizsgálatban nem talál-tak evidenciát arra vonatkozóan, hogy az ARB-vagy ACE-gátló kezelés fokozná a daganatspecifi kus mortalitást emlő-, colorectalis vagy prosztatatumor esetén [54].…”
Section: Klinikai Adatokunclassified